2009
DOI: 10.1111/j.1365-2222.2009.03307.x
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide and formoterol inhibit inflammatory mediator production by bronchial epithelial cells infected with rhinovirus

Abstract: BUD and FORM suppress RV-induced chemokines and growth factors in bronchial epithelial cells in a concentration-dependent, synergistic or additive manner. These data further support the combined use of BUD and FORM in asthma and COPD and intensification of this therapy during exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
55
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 35 publications
(42 reference statements)
7
55
1
3
Order By: Relevance
“…2006; Skevaki et al. 2009). We found evidence that low‐dose CHF6001 (10 −8  mol/L), when used together with FP (10 −9  mol/L), gave a greater suppressive effect than FP 10 −9  mol/L or high‐dose CHF6001 10 −6  mol/L.…”
Section: Discussionmentioning
confidence: 99%
“…2006; Skevaki et al. 2009). We found evidence that low‐dose CHF6001 (10 −8  mol/L), when used together with FP (10 −9  mol/L), gave a greater suppressive effect than FP 10 −9  mol/L or high‐dose CHF6001 10 −6  mol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, data from in vitro studies have suggested that the timing of administration of steroids has profound effects upon their ability to inhibit virus-induced cytokines. For example, in bronchial epithelial cells, rhinovirus-induced CXCL-10 was inhibited by budesonide when the drug was given at the start of the infection period [50], but not when applied 24 h prior to infection [51]. Quite how these in vitro results translate into clinical practice is uncertain.…”
Section: Are Corticosteroids Effective or Ineffective During Virus-rementioning
confidence: 99%
“…These effects are additive to, or even synergise with the anti-inflammatory effects of glucocorticosteroids [35][36][37][38] and include suppression of inflammatory responses induced by viral exposure [39][40][41] and anti-remodelling effects. Airway remodelling is an inherent component of asthma and includes increased numbers of airway smooth muscle cells, goblet cell hyperplasia and fibrotic rearrangement of the airway extracellular matrix.…”
Section: Airway Inflammation and Remodellingmentioning
confidence: 99%